Biosafety Level 4 Laboratory User Training Program, China - Xia, Han (Emerg Infect Dis, 2019)
Experienced, qualified personnel certified to work in high-level biocontainment laboratories contribute to the safe operation of these facilities. China began a training program for laboratory users after establishing its first Biosafety Level 4 laboratory, the Wuhan National Biosafety Laboratory (Level 4) of the Chinese Academy of Sciences. We provide an overview of the content of this training program, which can serve as a reference for developing national norms for high-containment laboratory training.